Not Just Ensemble Films: Six Degrees, Webs, Multiplexity and the Rise of Network Narratives - Vivien Silvey (University of Edinburgh, 2009)
In a scene from Alejandro Gonzalez Inarritu's 2006 film Babel, one afternoon a deaf-mute Japanese girl, Chieko, gossips in sign language with a school friend via her mobile phone's web cam. The scene's linguistically estranged nature encapsulates how language in itself is a technology, a system which reaches across borders of silence to allow understanding. We are only able to interpret language through shared knowledge of its systems and, in many cases, through the aid of devices which collapse the barriers of proximity in time, space, and in this case, vision. It is indicative of the contemporary paradigm of network society that this scene occurs within a film which explores worldwide repercussions of (mis)communication, and that Babel belongs within a genre which in recent years has frequently thematised systems of interconnection, exploiting digital narrative technologies and in effect practicing Fredric Jameson's concept "cognitive mapping" (Jameson 54). However, while they may appear to value difference and diversity, in many cases these films use cognitive mapping as a tool for totalisation, divulging narratives of smoothed-out differences and equalised circumstances. Within this emergent paradigm of interconnectedness continues the problem of how to relay the postmodern promise of endless complexity, without subordinating difference to a simplified reduction of totality.